Hardiness Pada Mahasiswa Yang Berwirausaha - Keke Herliany (Pusat Riset dan Inovasi Nasional, 2023)
This research obtained an overview of hardiness in students who are entrepreneurs. Hardiness has a very important and influential role for entrepreneurial students. This research uses a qualitative approach with case study analysis. The subjects of the study were selected using the purposive sampling method. A total of three people were selected as the main subjects based on the variety of subjects obtained at the time of the initial exploration. Case study analysis was carried out on data from interviews, field notes, and observations. It was found that, commitment, control, and challenges affect hardiness in entrepreneurial students.